The efficacy, safety, and pharmacokinetics/pharmacodynamics of telitacicept following efgartigimod in generalized myasthenia gravis: protocol of a randomized controlled trial - Li, Jia; Zhang, Yuan; Deng, Yan; Li, Wenyu; Wang, Yiqi; Qi, Feiteng; Zhang, Qiaoyi; Wan, Bingbing; Li, Xiang; Weng, Yiyun; Fang, Zheyu; Zhang, Yu; et al. (Frontiers in Immunology, 2025)
IntroductionSeveral biologic agents have emerged as novel therapeutic options for patients with generalized myasthenia gravis (gMG); however, no clinical studies have yet explored the efficacy and safety of sequential biologic therapy in gMG.Methods and analysisThis multicenter, open-label, randomized controlled, exploratory clinical trial plans to enroll 60 patients with acetylcholine receptor antibody-positive gMG, randomized in a 1:1:1 ratio to receive one of the following treatment regimens: (1) E + 1w+T: efgartigimod 10 mg/kg weekly for 4 weeks, followed by telitacicept 240 mg weekly starting 1 week after the last efgartigimod dose, continued for 25 weeks; (2) E + 2w+T: efgartigimod as above, followed by telitacicept 240 mg weekly starting 2 weeks after the last efgartigimod dose, continued for 24 weeks; or (3) T only: telitacicept monotherapy for 30 weeks. The primary endpoint is the change in the Quantitative Myasthenia Gravis (QMG) score from baseline to week 30. Secondary endpoints include changes in the Myasthenia Gravis Activities of Daily Living (MG-ADL) score from baseline, proportion of patients achieving minimal manifestation status (MMS), changes in dosages of corticosteroid and other immunosuppressant, rates of MG relapse/acute exacerbation and MG crisis, and safety outcomes. The pharmacokinetics/pharmacodynamics (PK/PD) of telitacicept will also be assessed. Recruitment is currently ongoing, but no participants have been enrolled as of yet.Ethics and disseminationThe study has been approved by the Ethics Committee in Clinical Research of the First Affiliated Hospital of Wenzhou Medical University. Results of the study will be disseminated to the relevant scientific, clinical and patient communities on trial closure. Trial registration number: The study was registered at ClinicalTrials.gov (NCT06827587).